THE PRACTICE OF LONGITUDINALITY IN ATTENDANCE OF CHILDREN'S HEALTH: COMPARISON BETWEEN DISTINCT CARE MODELS - Vanessa Comassetto Oliveira; Maria de La Ó Ramallo Veríssimo (Universidade Federal do Paraná, 2015)
The orientation of the primary healthcare services was evaluated in the perspective of longitudinality in children's healthcare. A transversal study with a quantitative approach was undertaken in the units with the Family Health Strategy and of the traditional model in the Primary Care Units. The data were raised through interviews held between June and July 2012, with families of children (n=482), and were analyzed using the Primary Care Assessment Tool. It was observed that long-duration personal relationships between the health professionals and the patients and family members is weakened in both models of care. The units of the Family Health Strategy obtained a score above the cut-off value in two of 11 items of the attribute 'longitudinality'. The Primary Healthcare Units had all the items with scores below the value. The principle of longitudinality was not shown to be incorporated, and its practice, as a principle of the Unified Health System, continues to be a challenge in both the models of care.